Recognition of emotional expressions of a face depending on the professional activity of an observer: an experimental study - T. Todić Jakšić; M. Pavićević (Психологическая наука и образование)
Context and relevance. In addition to the biological adaptive function, emotions have a significant socio-psychological and communicative role. Accurate recognition of facial expressions and gestures is of great importance for successful communication in social interactions. Objective. The research aimed to determine the differences in the accuracy of emotion recognition, based on facial expression, between students of the Faculty of Medicine (FM) and students of the Faculty of Technical Sciences (FTS). Hypothesis. It is assumed that faculty students from helping professions (FM) will recognize emotions more accurately than faculty students from the field of non-helping professions (FTS). Methods and materials. The sample consisted of students of both genders (N = 145, of which 74 were from the FM, and 71 from the FTS). The Japanese and Caucasian Facial Expressions of Emotion (JACFEE) instrument was used in the research, which contains 56 photos, i.e. eight photos for each of the seven emotions: anger, contempt, disgust, fear, happiness, sadness and surprise. Results. Respondents studying FM are more successful in accurately recognizing emotions such as anger, contempt, disgust, fear, and surprise compared to respondents studying FTS. However, subjects studying at FTS are more successful in the accuracy of recognizing the emotion of happiness compared to subjects studying FM. In the accuracy of recognizing the emotion of sadness, there is no statistically significant difference between these two groups of respondents. Conclusions. Based on the obtained data, it can be assumed that students who chose a faculty related to the provision of medical services are more interested in people, their emotional state and social interaction. Perhaps, such students have a deeper understanding of interpersonal interaction than students studying in the faculties of non-helping professions, which are more oriented towards working with objects.